2013
DOI: 10.1093/molbev/mst264
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Costs of Minimal Sequence Alterations Causing Protein Instability and Toxicity

Abstract: Destabilization of a protein impairs its metabolic efficiency. It is less clear how often destabilization also results in a gain of toxicity. We derived collections of temperature-sensitive, and thus structurally unstable, mutants of the yeast ADE2 and LYS2 genes by introducing single or very few amino acids substitutions. Overexpression of these mutant proteins led to a common, although unequal, fitness decrease. Interestingly, although the mutant proteins were functionally redundant, higher expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
2
9
1
Order By: Relevance
“…5). Despite the previously reported associations between increased protein stability and lower aggregation rates, higher soluble abundance and a greater capacity to evolve (DePristo et al 2005;Bershtein et al 2012;Tomala et al 2014;Bloom et al 2006), we found no statistically significant correlation, either positive or negative, between the measures of LeuB stability (T opt and DG z NÀU ) and organism fitness (Fig. 5).…”
Section: In Vivo Fitness Is Not Correlated With Stability or Catalyticontrasting
confidence: 99%
See 1 more Smart Citation
“…5). Despite the previously reported associations between increased protein stability and lower aggregation rates, higher soluble abundance and a greater capacity to evolve (DePristo et al 2005;Bershtein et al 2012;Tomala et al 2014;Bloom et al 2006), we found no statistically significant correlation, either positive or negative, between the measures of LeuB stability (T opt and DG z NÀU ) and organism fitness (Fig. 5).…”
Section: In Vivo Fitness Is Not Correlated With Stability or Catalyticontrasting
confidence: 99%
“…In turn, soluble protein abundance was positively correlated with organism fitness. Tomala et al (2014) also showed that overexpression of destabilised mutants of two yeast proteins was associated with decreased fitness. Thirdly, increased protein stability has been associated with mutational robustness, or a greater capacity to sample sequence space in the course of evolution (Bloom et al 2005(Bloom et al , 2006.…”
Section: Introductionmentioning
confidence: 97%
“…Various studies have reported diverse and often conflicting effects in terms of the beneficial and detrimental effects of protein deposit formation on cell fitness (Maji et al , ; Geiler‐Samerotte et al , ; Sanchez de Groot et al , ; Escusa‐Toret et al , ; Tomala et al , ). These differences are understandable if one considers the complexity of deposit formation, the differences in the dynamic nature of the deposit, biochemical function of the protein forming the deposit, and the diversity in the experimental conditions in which the studies have been carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we measure and disentangle the effects of phase separation of a model protein. To trigger the phase separation process, instead of mutating an endogenous protein to destabilize it as has been done before (Geiler‐Samerotte et al , ; Tomala et al , ), we designed a modular system that allows us to disentangle and quantify the cost/benefit of protein phase separation while tuning different roles influencing this process (e.g., the essentiality/non‐essentiality/toxicity of a protein). The model protein phase‐separates from a mainly soluble, functionally active state into a primarily insoluble, functionally less active state (Materials and Methods, Figs 5 and EV1, and Appendix Fig S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation